Functional Outcomes of Arteriovenous Fistulas Created by Nephrologist - Shrestha, S.; Soni, S.S.; Vachharajani, T.J. (Kathmandu University Medical Journal, 2020)
Background Nephrologists worldwide, after undergoing surgical training, have reported creating arteriovenous fistulas (AVFs). Objective To demonstrate the functional outcome of arteriovenous fistulas created by a trained Nepalese nephrologist. Method This was a cross sectional study. A convenient sampling method was used and all consecutive AVFs created by a single nephrologist from January 2016 to December 2018 were included to assess their functional status within 3 months of creation. Patients with incomplete data and no follow up for up to 3 months post surgery were excluded. Result One hundred sixty six (166) arteriovenous fistulas were created during the study period; mean age of the patients was 52 ± 14 years, 121 (75%) male and 65 (39%) were diabetic. The most common site of arteriovenous fistula creation was left radiocephalic (Lt RC) 69(41.5%), followed by left brachiocephalic (Lt BC) 66(39.7%). Other sites were left brachiobasilic (Lt BB) 10(6%), right brachiocephalic (Rt BC) 10(6%), right radiocephalic (Rt RC) 9(5.4%) and right brachiobasilic (Rt BB) 2(1.2%). 139 arteriovenous fistulas (83.7%) were functional within 3 months post creation. Functional outcomes of radiocephalic, brachiocephalic and brachiobasilic arteriovenous fistulas were 75.6%, 90.7% and 100% respectively at 3 months post creation. Lymphoceles developed in three Lt BC arteriovenous fistulas, thrombosis in two Lt BC arteriovenous fistulas and infection in two Lt BC arteriovenous fistulas with pseudoaneurysm formation. Conclusion The functional outcome of arteriovenous fistulas created by a trained Nepalese nephrologist is similar to that reported in the literature.